Precipitation responses to ENSO and IOD in the Maldives: Implications of large-scale modes of climate variability in weather-related preparedness. (November 2020) - Foley, Aideen; Kelman, Ilan
Abstract: This research seeks to address the extent to which indices of large-scale modes of climate variability (El Niño Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD)) can be linked to physical differences in the local mean and extreme rainfall conditions experienced in the Maldives in order to suggest implications for disaster risk reduction (DRR). While some significant differences in precipitation metrics do occur at the local level between different phases of the large-scale modes of climate variability studied, they do not occur for all sites studied. While the constrained availability of historical meteorological data in the region is a limiting factor in this analysis, these findings suggest that with respect to decision-making related to extreme precipitation, ENSO/IOD forecasting may be most helpful on local scales, when supplementing an approach of on-going readiness in which communities are prepared to effectively manage hazards in any phase of the large-scale modes of climate variability studied. These conclusions are based on only precipitation; results may vary for other impacts including changing sea levels and sea surface temperatures.